Simplified design procedure for frame buildings with viscoelastic or elastomeric structural dampers. - Lee, Kyung-Sik
A simplified design procedure (SDP) for preliminary seismic design of frame buildings with structural dampers is presented. The SDP uses elastic static analysis and is applicable to structural dampers made from viscoelastic (VE) or high damping elastomeric materials. The behaviour of typical VE materials and high damping elastomeric materials is often non-linear and the SDP idealizes these materials as linear VE materials. With this idealization, structures with VE or high damping elastomeric dampers can be designed and analysed using methods based on linear VE theory. As an example, a retrofit design for a typical non-ductile concrete (RC) frame building using high damping elastomeric dampers is developed using the SDP. To validate the SDP, results from non-linear dynamic time history analyses (NDTHA) are presented. Results from NDTHA demonstrate that the SDP estimates the seismic response with sufficient accuracy for design. It is shown that a non-ductile RC frame building can be retrofit with high damping elastomeric dampers to remain essentially elastic under the design basis earthquake (DBE).
Keywords: Structural damper; Viscoelastic damping material; Elastomeric damping material; Seismic design and analysis; Performance based design; Seismic retrofit